Impact of China's urban resident basic medical insurance on health care utilization and expenditure - Hong Liu; Zhong Zhao (Institute for the Study of Labor (IZA), 2012)
In 2007, China launched a subsidized voluntary public health insurance program, the Urban Resident Basic Medical Insurance, for urban residents without formal employment, including children, the elderly, and other unemployed urban residents. We estimate the impact of this program on health care utilization and expenditure using 2006 and 2009 waves of the China Health and Nutrition Survey. We find that this program has significantly increased the utilization of formal medical services. This result is robust to various specifications and multiple estimation strategies. However, there is no evidence that it has reduced out-of-pocket expenditure and some evidence suggesting that it has increased the total health care expenditure. We also find that this program has improved medical care utilization more for the elderly, for the low- and middle-income families, and for the residents in the relatively poor western region.
Keywords: I13; G22; H43; 330; urban China; health insurance; health care utilization; health expenditure; Gesetzliche Krankenversicherung; Subvention; Basisgesundheitsversorgung; Gesundheitskosten; Stadtbevölkerung; China